Pengaruh likuiditas dan Leverage Terhadap Nilai Perusahaan: Studi Kasus pada Perusahaan Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Yasmita Eyato; Srie Isnawaty Pakaya; Meriyana Franssisca Dungga (Economic Reviews Journal, 2024)
This study aims to find out how the Current Ratio and Debt To Equity Ratio affect Company Value. in companies in the Basic Industry and Chemical Sector listed on the Indonesia Stock Exchange for the 2018-2022 period. The research method used is qualitative and sampling techniques using Purpisive sampling with the number of samples obtained in this study as many as 40 companies from 73 companies in the basic and chemical industry sectors. The data collection technique in this study uses secondary data, namely financial report data that has been published by companies in the basic industry and chemical sectors on the Indonesia Stock Exchange (IDX). Based on the results of the test, it shows that partially the Current ratio (CR) has a positive effect on the Company's Value. Debt To Equity Ratio has a negative effect on the Company's Value. The results of the study also show that simultaneously the Current Ratio (CR) and Debt To Equity ratio (DER) have an effect on the Company's Value.